2018
DOI: 10.1371/journal.pone.0202034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of six decontamination procedures for isolation of Mycobacterium avium complex from avian feces

Abstract: Culture is considered the gold standard for definitive diagnosis of mycobacterial infections. However, consensus about the most suitable culture procedure for isolation of nontuberculous mycobacteria is lacking. The study compared the recoveries of mycobacteria after decontamination of spiked and fresh avian feces with 4% sodium hydroxide (NaOH), 12% sulfuric acid (H2SO4), or 1% cetylperidinium chloride (CPC), with and without mixture of three antibiotics, namely vancomycin (VAN, 100 μg/ml), nalidixic acid (NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…Both culture-dependent and independent approaches rely on the intrinsic characteristics of the type of matrices tested. The isolation of mycobacteria, namely the slow-growing, is very difficult from microbially rich environments, for which harsh decontamination is recommended [ 317 ]. In addition, the intrinsic characteristics of several species of Mycobacterium require specific micronutrients (e.g., M. haemophilum ), growth enhancers (e.g., M. genavense ), optimal pH, temperature, and oxygen levels, which allied to a particular sensibility to decontamination (e.g., M. ulcerans ) sets obstacles to bacteriological isolation [ 252 , 318 ].…”
Section: Detection Identification and Differentiation Tools For mentioning
confidence: 99%
“…Both culture-dependent and independent approaches rely on the intrinsic characteristics of the type of matrices tested. The isolation of mycobacteria, namely the slow-growing, is very difficult from microbially rich environments, for which harsh decontamination is recommended [ 317 ]. In addition, the intrinsic characteristics of several species of Mycobacterium require specific micronutrients (e.g., M. haemophilum ), growth enhancers (e.g., M. genavense ), optimal pH, temperature, and oxygen levels, which allied to a particular sensibility to decontamination (e.g., M. ulcerans ) sets obstacles to bacteriological isolation [ 252 , 318 ].…”
Section: Detection Identification and Differentiation Tools For mentioning
confidence: 99%
“…Previous studies have shown that time for samples processing is important factor affecting primary isolation of mycobacteria [18]. Given that our previous study [24] reported that CPC-VNA can control the contamination rate of L-J cultures better than other methods, we postulate that the contamination rate (27.9%) of L-J cultures in this study is acceptable.…”
Section: Discussionmentioning
confidence: 65%
“…Although the recovery of mycobacteria on L-J culture was very low, we postulate that this low isolation rate may reflect the real occurrence of mycobacteria in chickens and birds. Furthermore, CPC-VNA decontamination method may has a favorable impact on culture sensitivity by reducing the contamination rate [14,[23][24][25]36] and increasing the number of positive AFB culture. Isolation of environmental mycobacteria like M. avium, M. terrae and M. engbaekii, which do not possess IS901, may not be pathogenic to the birds because no clinical relevance of these species have been reported [38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations